2015
DOI: 10.15678/znuek.2015.0947.1102
|View full text |Cite
|
Sign up to set email alerts
|

Material Deprivation in Poland and Slovakia – a Comparative Analysis

Abstract: One of the key targets of the EU's 2020 Strategy is to substantially reduce the number of people at risk of poverty or social exclusion. The EU seeks to reduce poverty by lifting at least 20 million people out of the risk of poverty or social exclusion by 2020. The monitoring of progress towards this target is based on the headline indicator AROPE-people at risk of poverty or social exclusion. The indicator applies to people either at risk of poverty or severely materially deprived or living in a household wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
2
9
0
Order By: Relevance
“…Furthermore, our findings confirm the importance of such attributes of the household head as age, educational attainment, economic activity, and occupational position. Specifically, as other studies have shown (Nelson 2012;Bárcena-Martín et al 2014;Šoltés and Ulman 2015;Israel 2016;Bárcena-Martín et al 2019), our results prove that MD varied substantially for different age groups. Households reported being more materially deprived when they were younger than when they were older.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Furthermore, our findings confirm the importance of such attributes of the household head as age, educational attainment, economic activity, and occupational position. Specifically, as other studies have shown (Nelson 2012;Bárcena-Martín et al 2014;Šoltés and Ulman 2015;Israel 2016;Bárcena-Martín et al 2019), our results prove that MD varied substantially for different age groups. Households reported being more materially deprived when they were younger than when they were older.…”
Section: Discussionsupporting
confidence: 87%
“…The literature provides consistent findings in all countries that higher education reduces MD (Bárcena-Martín et al 2019;Israel 2016;Nelson 2012;Šoltés and Ulman 2015). Unemployed persons, those living alone, and single parents are more vulnerable to MD (Bárcena-Martín et al 2014;Israel and Spannagel 2019;Hicks 2016;Nelson 2012;Šoltés and Ulman 2015). Other socio-demographic factors such as gender, age, health status, and place of residence have also been examined by many authors.…”
Section: Correlates Of Materials Deprivation In the Eumentioning
confidence: 74%
See 3 more Smart Citations